Microbiome Profile of Dogs with Stage IV Multicentric Lymphoma: A Pilot Study - Feriel Yasmine Mahiddine; Inhwan You; Heekee Park; Min Jung Kim (Veterinary Sciences, 2022)
Changes in the gut microbiome can be associated with diseases and affect the overall health of an individual. In the current study, the gut microbiome profile of dogs diagnosed with advanced stages of multicentric lymphoma was compared with that of healthy dogs and analyzed. For this purpose, dogs from veterinary hospitals diagnosed with lymphoma were selected and were further narrowed down to cases of stage IV multicentric lymphoma. Fecal samples from the selected sick and healthy dogs were collected and analyzed using MiSeq sequencing. The gut microbiota in the two groups of dogs was statistically analyzed and compared. The results revealed significant differences in the microbial populations present in sick and healthy dogs. Phylum Actinobacteria and two species (Corynebacterium amycolatum and Streptococcus lutetiensis) were found in high proportions in sick dogs and may be considered as potential biomarkers for canine stage IV multicentric lymphoma. Further investigations need to be conducted to understand the mechanisms they might be involved in.